A Note on the Quadrilateral Mesh Condition $RDP(N,ψ)$ (Journal of Computational Mathematics, 2018)
The main aim of this paper is to show that the quadrilateral mesh condition $RDP(N,ψ)$ is only sufficient but not necessary for the optimal order error estimate of the $Q_{1}$ isoparametric element in the $H^{1}$ norm.
Keywords: Isoparametric finite element; Optimal order error estimate; Quadrilateral mesh condition.